Bilateral resorption of mandibular angle in patient with systematic sclerosis - a case report - Karolina Futyma-Gąbka; Magdalena Piskórz; Ingrid Różyło-Kalinowska (Kazimierz Wielki University, 2022)
Progressive systemic sclerosis (PSS) is chronic autoimmune disease affecting a connective tissue. The symptoms of PSS in orofacial area are: restricted mouth opening, xerostomia, facial asymmetry and problems with oral hygiene. Radiographic images can show specific features like bone resorption, especially in mandibular region or periodontal ligament space widening. The aim of this study was to present the case of 56-year-old woman with characteristic scleroderma-related changes visible on panoramic radiograph. The patient diagnosed with severe systemic sclerosis was referred by dermatologist to general dentist. The woman experienced tightening of facial skin, xerostomia and reduced mouth opening which caused problems with daily oral hygiene and dental treatment. General dentist referred the patient to the Department of Dental and Maxillofacial Radiodiagnostics of Medical University of Lublin for the panoramic X-ray. One of the main findings was bilateral resorption of mandibular angles. Localization of the bone resorption in patients with scleroderma is related to attachements of masticatory muscles. Dentists and general doctors should be aware that some of the maxillofacial manifestations of systematic scleroderma can be visible on panoramic radiographs.